2022
DOI: 10.3389/fcell.2022.836913
|View full text |Cite
|
Sign up to set email alerts
|

Integration Analysis of Transcriptome and Proteome Reveal the Mechanisms of Goat Wool Bending

Abstract: Zhongwei goat is a unique Chinese native goat breed for excellent lamb fur. The pattern of flower spikes of the lamb fur was significantly reduced due to the reduction of the bending of the hair strands with growth. In order to explore the molecular mechanism underlying hair bending with growth, we performed the comprehensive analysis of transcriptome and proteome of skins from 45-days, 108-days and 365-days goat based on TMT-based quantitative proteomics and RNA-seq methods. In the three comparison groups, 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
(46 reference statements)
1
4
0
Order By: Relevance
“…Among these DMG, KRT71 and CD44 were highly methylated in one-month-old lambs, whereas ROR2 and ZDHHC13 were highly methylated in 48-month-old sheep. Interestingly, a similar phenotype of curly fibers was also found in goats [138][139][140][141]. Further information on the curly fleece phenotype in sheep is provided in Additional file 2: Table S11.…”
Section: Curly Fleecesupporting
confidence: 60%
“…Among these DMG, KRT71 and CD44 were highly methylated in one-month-old lambs, whereas ROR2 and ZDHHC13 were highly methylated in 48-month-old sheep. Interestingly, a similar phenotype of curly fibers was also found in goats [138][139][140][141]. Further information on the curly fleece phenotype in sheep is provided in Additional file 2: Table S11.…”
Section: Curly Fleecesupporting
confidence: 60%
“…Functional enrichment analysis of DEIs revealed significant enrichment in pathways related to hair follicle and skin development. For example, the extracellular matrix-mediated crosstalk of multiple signaling pathways has been shown to regulate the density of hair follicles in sheep and wool bending in goats [37,39]. It has been reported that enhanced focal adhesion can decrease cell migration in focal adhesion kinase-deficient mice [40], and the transition stage from telogen to anagen is associated with focal adhesion [41].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, Protein digestion and absorption, Metabolic pathways, PI3K-Akt signaling pathway, ECMreceptor interaction, and Relaxin signaling showed their pivotal roles in orchestrating collagen deposition within the dermal matrix, skin development, extracellular matrix and collagen fibril organization of Dezhou donkey skin (Table 2). Interestingly, a recent study found several important signaling pathways related to wool growth and bending, such as ECM-receptor interaction, PI3K-Akt signaling pathway, Relaxin signaling pathway, protein digestion and absorption, and metabolic pathways in Zhongwei goats (He et al, 2020;Liu et al, 2022). In addition, a recent experimental trial has shown that PI3K-Akt signaling pathway, Protein digestion and absorption and ECM−receptor interaction signaling pathways were associated with regulation of actin filament-based process, regulation of actin cytoskeleton organization, cell-matrix adhesion and collagen fibril Collagen Alpha family genes regulate protein digestion and absorption signaling pathway.…”
Section: Discussionmentioning
confidence: 99%